(untitled) (Archives of Pediatrics of Uruguay, 2023)
Introduction: pain treatment is a human right and a pillar of palliative care (PC). This symptom in children is often underestimated and insufficiently treated. Objective: learn about the prevalence of pain and describe the analgesic drugs’ usage profile, adjuvants and invasive procedures in children assisted in the Pediatric Palliative Care Unit of the Pereira Rossell Hospital Center (UCPP-CHPR) during the period 2019-2021. Methodology: observational, descriptive and retrospective study based on the review of medical records. Results: 317 children were included, 58% male, with a median age of 6.9 years. 64% were carriers of severe non-progressive neurological diseases, 51% used prosthetics or medical technology. A record of the presence of pain was found in 35%, chronic type 87%, mixed 55% and multiple sources 54%. The use of a pain assessment scale was detected in 61%, the most used was r-FLACC. In the group of children with pain, analgesics were prescribed in 43% (48/111) and adjuvants in 87% (97/111), gabapentin in 78. In all of them, the administration route was oral/enteral. Off-label use of drugs was found in 79% and polypharmacy in 82%. Adverse effects were recorded in 10%. Conclusion: a third of the children assisted by the UCPP-CHPR showed records of pain presence. Most chronic type, mixed and multiple sources. We found a vast use of validated scales for pain assessment and high prescription of adjuvants in relation to analgesics.